Pergaulan bebas di kalangan remaja yang mengubah norma sosial di era modernisasi: Perspektif Q.S An-nur ayat 30-31 - didin, Izzuddin didin (Maliki Interdisciplinary Journal, 2025)
The phenomenon of promiscuity among Indonesian teenagers shows an increasingly high level of social deviance along with the flow of modernization, cultural globalization, and advances in information technology. Boundless interaction between men and women outside the bonds of marriage has normalized practices such as free sex, intensive dating, and pregnancy outside marriage. It aims to examine how promiscuity causes a shift in social norms in society, as well as how the Qur'anic solution, especially Q.S. An-Nur verses 30-31, becomes a corrective instrument in fortifying adolescent morality. The method used is a literature review with a Systematic Literature Review (SLR) approach, through analysis of various academic sources and scientific publications that are relevant in the current context. The results showed that modernization has led to a weakening of religious values in adolescent social interactions. Social norms that once denounced promiscuity have now shifted to popular culture. Q.S. An-Nur verses 30-31 not only explicitly prohibits promiscuity, but also instructs men and women to lower their gaze, keep their aurat, and not show their adornment to non-mahrams. The commentaries of Sayyid Quthub and Sheikh Abdul Latif Syakur emphasize the importance of faith-based sex education as the main bulwark for preventing sexual deviance. Therefore, moral and religious education should start from the family and be reinforced through schools and value-conscious social environments. Islam offers solutions not only in the form of prohibition, but also through an integrative educational, spiritual and social approach. With this approach, it is hoped that the younger generation will have moral resilience in the face of the onslaught of permissive cultures that undermine societal norms.